Comparison of lumen-apposing metal stents versus double-pigtail plastic stents for infected necrotising pancreatitis. Issue 1 (14th June 2022) - Boxhoorn, Lotte; Verdonk, Robert C; Besselink, Marc G; Boermeester, Marja; Bollen, Thomas L; Bouwense, Stefan AW; Cappendijk, Vincent C; Curvers, Wouter L; Dejong, Cornelis H; van Dijk, Sven M; van Dullemen, Hendrik M; van Eijck, Casper HJ; et al.
Abstract : Objective: Lumen-apposing metal stents (LAMS) are believed to clinically improve endoscopic transluminal drainage of infected necrosis when compared with double-pigtail plastic stents. However, comparative data from prospective studies are very limited. Design: Patients with infected necrotising pancreatitis, who underwent an endoscopic step-up approach with LAMS within a multicentre prospective cohort study were compared with the data of 51 patients in the randomised TENSION trial who had been assigned to the endoscopic step-up approach with double-pigtail plastic stents. The clinical study protocol was otherwise identical for both groups. Primary end point was the need for endoscopic transluminal necrosectomy. Secondary end points included mortality, major complications, hospital stay and healthcare costs. Results: A total of 53 patients were treated with LAMS in 16 hospitals during 27 months. The need for endoscopic transluminal necrosectomy was 64% (n=34) and was not different from the previous trial using plastic stents (53%, n=27)), also after correction for baseline characteristics (OR 1.21 (95% CI 0.45 to 3.23)). Secondary end points did not differ between groups either, which also included bleeding requiring intervention—5 patients (9%) after LAMS placement vs 11 patients (22%) after placement of plastic stents (relative risk 0.44; 95% CI 0.16 to 1.17). Total healthcare costs were also comparable (mean difference −€6348, bias-corrected and accelerated 95% CI −€26 386 to €10 121). Conclusion: Our comparison of two patient groups from two multicentre prospective studies with a similar design suggests that LAMS do not reduce the need for endoscopic transluminal necrosectomy when compared with double-pigtail plastic stents in patients with infected necrotising pancreatitis. Also, the rate of bleeding complications was comparable.